A lepto-hadronic model for the high energy emission from the jets of FR I radiogalaxies - Reynoso, Matias Miguel (2011)
We present a lepto-hadronic model for the VHE emission from the relativistic jets of FR I radiogalaxies. We assume that protons and electrons are accelerated in a compact region near the base of the jet, and they cool emitting multiwavelength radiation as they propagate along the jet. The particle distributions are obtained using an inhomogeneous steady-state transport equation that accounts for the cooling processes as well as the convection of particles in the jet. The dominant processes that contribute to the photon SED are electron and proton synchrotron radiation, inverse Compton interactions, and the inelastic collisions pp and pã. The accompanying neutrino output is obtained and the possibility of detection with Km3Net and IceCube is discussed for the cases of Cen A and M87.